Cadetes of the Academia do Polícia Militar do Estado do Rio de Janeiro Correlación entre VO2 max, gordura relativa y perfil lipídico, en cadetes de la Academia de Policía Militar del Estado de Río de Janeiro - E. H. M. Dantas; L. Sarmiento; M. L. D. Ferrão; R. G. S. Vale; A. S. Rabelo; M. J. S. Silva (Asociación Española de Ciencias del Deporte, 2010)
The objective of the present study was to verify the correlation level among the max, the relative fat and the profile lipídico of 51 Cadets (Age = 23.63 3.58 years; Weight = 74.13 ± 10.46 kg; Height = 1.76 ± 0.06 m; IMC = 23.99 2.76 kg/m2), of the masculine gender, of the Academy of the Military police of the State of Rio de Janeiro, of the year of 2007. The subjects were active and participants of the military physical training (TFM) accomplished five times a week, with duration of 60 minutes for session. They were appraised: the max for ergoespirometria (I record of progressive effort, with constant inclination of 3% and initial speed of 4,0km/h), the relative fat (% G - I record of three cutaneous folds) and the profile lipídico, through the method Enzymatic Calorimétrico in the variables: total cholesterol (CT), triglicérides (TG), lipoproteína of density high-cholesterol (HDL-C) and lipoproteína of density low-cholesterol (LDL-C). The test of correlation of Spearman presented correlation significant between max and TG (r = -0,289; p = 0,04),  max and HDL-C (r = 0,277; p = 0,049),% G and TG (r = 0,296; p = 0,035),% G and HDL-C (r = 0,338; p = 0,015). Like this, these discoveries point a discreet relationship between the profile lipídico and the maximum consumption of oxygen corroborating the need to consider other factors as the feeding and the intensity of the exercises in the investigation of this relationship. Key Words: training,  VO2 max, relative fat, lipidic profile.   El objetivo del presente estudio es establecer el nivel de correlación entre el  VO2 max, la grasa relativa y el perfil lipídico de 51 cadetes varones (Edad = 23.63 ± 3.58 años; Peso = 74.13 ± 10.46 Kg.; Talla = 1.76  ± 0.06 m; IMC = 23.99 ± 2.76 Kg. /m2) de la Academia de la Policía Militar del Estado de Río de Janeiro, del año de 2007. Los sujetos son físicamente activos y realizan entrenamiento físico militar (TFM) cinco veces a la semana, con una duración de 60 minutos por sesión. Los parámetros evaluados son: el VO2 max por ergo espirometría (protocolo de esfuerzo progresivo, con inclinación constante de 3% y velocidad inicial de 4,0km/h), la grasa relativa (% Grasa – protocolo de tres pliegues cutáneos) y el perfil lipídico mediante el método Calorimétrico Enzimático para las variables: colesterol total (CT), triglicéridos (TG), lipoproteína de densidad alta-colesterol (HDL-C) y lipoproteína de densidad baja-colesterol (LDL-C). El test de de Spearman presentó correlación significativa entre  VO2 max y TG (r= -0,289; p= 0,04), VO2 max y HDL-C (r= 0,277; p= 0,049),  %G y TG (r= 0,296; p= 0,035),  %G y HDL-C (r= 0,338; p= 0,015). Los resultados del estudio apuntan a una discreta relación entre el perfil lipídico y el consumo máximo de oxígeno y corroboran la necesidad de considerar otros factores como: alimentación e intensidad del esfuerzo realizado para aumentar la solidez de este estudio. Palabras Clave: entrenamiento,  VO2 max, grasa relativa y perfil lipídico.